Radiation from frequent whole-body CT scans induces systemic immunosuppression and immune activation of tumor tissue - Jigang Dong; Chengrui Fu; Minghao Li; Zhongtang Wang; Baosheng Li (Translational Oncology)
Abstracts: Objective: This study aims to elucidate the impact of repeated whole-body computed tomography (CT) scans on systemic immunity, the tumor immune microenvironment, and tumor control. This inquiry was prompted by clinical observations indicating a decrease in the levels of IFN-β and IFN-γ in patients' blood following whole-body CT scans. Methods: A Lewis lung carcinoma (LLC) mouse model was established and divided into two groups: a control group and a group subjected to multiple whole-body CT scanning radiation (WBCTSs). The study monitored tumor growth trends across both groups and employed a comprehensive set of analytical techniques—including enzyme-linked immunosorbent assay (ELISA), flow cytometry analysis, immunohistochemistry, RNA sequencing, and single-cell sequencing—to assess differences in cytokine profiles (IFN-β and IFN-γ), proportions of key immune cells, and gene expression variations between the groups. Results: Repeated CT scan radiation does not promote tumor progression. In tumor tissues subjected to multiple CT scans, an increase in the proportion of CD8+ T cells, elevated interferon levels, and up-regulation of genes associated with killing in CD8+ T cells and genes associated with Ifnb in macrophages were observed. In contrast, radiation from multiple whole-body CT scans resulted in a decrease in the proportion of CD8+ T cells in the blood and spleen, a decrease in serum interferon levels, and down-regulation of killing-related genes in CD8+ T cells. Conclusion: Our results suggest that repeated whole-body CT scanning radiation induces systemic immunosuppression and immune activation in tumor tissues. Multiple repeated CT scans do not promote tumor progression.